2010
DOI: 10.1002/aqc.1147
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of different salmonid strains as hosts for the endangered freshwater pearl mussel (Margaritifera margaritifera L.)

Abstract: ABSTRACT1. The complex life cycle of endangered European freshwater pearl mussel Margaritifera margaritifera L. involves an obligatory parasitic phase on a host fish. Knowledge on the host-parasite interaction and on the suitability of different host fish species and strains is required both for the management of wild fish and mussel populations as well as for improving the efficiency of captive breeding methods.2. In this study, the suitability of different salmonid strains for hosting glochidia was tested, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 20 publications
5
106
1
Order By: Relevance
“…The fact that larger hosts can carry greater numbers of glochidia could be explained by their more intense respiration and greater water uptake as well as their greater gill surface area. The same size-dependent pattern within one age class of fish hosts was also previously observed in the pearl mussel-brown trout relationship (Taeubert et al, 2010). Surprisingly, despite their expected immunity, older hosts also carried great numbers of glochidia, which could be explained by their lack of previous contact with pearl mussel glochidia or an incomplete immunity.…”
Section: Discussionsupporting
confidence: 76%
“…The fact that larger hosts can carry greater numbers of glochidia could be explained by their more intense respiration and greater water uptake as well as their greater gill surface area. The same size-dependent pattern within one age class of fish hosts was also previously observed in the pearl mussel-brown trout relationship (Taeubert et al, 2010). Surprisingly, despite their expected immunity, older hosts also carried great numbers of glochidia, which could be explained by their lack of previous contact with pearl mussel glochidia or an incomplete immunity.…”
Section: Discussionsupporting
confidence: 76%
“…The species has a complex life cycle including an obligate parasitic stage on suitable host fish and a juvenile phase in the interstitial zone (Taeubert et al, 2010;Young and Williams, 1984). The most sensitive life stage appears to be the early post-parasitic phase, during which the juveniles need a stable, but well oxygenized interstitial for up to 5 years (Buddensiek et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on both these subjects are scarce and contradictory. A higher infectivity of glochidia in brown trout originating from a FPM habitat than elsewhere was found by Taeubert et al (2010) and Jung et al (2013), while in the study of Österling and Larsen (2013) a non-local brown trout strain was the most intensively infected fish. Brook trout is suggested to be a suitable FPM host in the USA (Clarke and Berg 1959, Athearn and Clarke 1962, Smith 1976), but not in Germany (Bauer 1987c) or Austria (Jung et al 2013).…”
Section: The Interactions Between the Freshwater Pearl Mussel And Hosmentioning
confidence: 61%
“…However, this impression has been questioned recently, because differences in the suitability of either of these well-known hosts for certain FPM populations have been found in Norway (Karlsson et al 2014) and Sweden (Österling and Wengström 2015). Furthermore, Taeubert et al (2010) and Österling and Larsen (2013) demonstrated differences between different strains of brown trout in their suitability as FPM host. Thus, for conservation of FPM, and for better understanding the interactions between FPM and salmonids, there is a need for wider investigation of the potential host specificity, especially in northernmost Europe which harbours the most important FPM populations in terms of high genetic diversity (Geist andKuehn 2008, Geist et al 2010).…”
Section: The Interactions Between the Freshwater Pearl Mussel And Hosmentioning
confidence: 99%